Adult Spinal Cord Injury Without Radiographic Abnormality (SCIWORA). Two case reports and a narrative review. - Bonfanti, Laura; Donelli, Valentina; Lunian, Marco; Cerasti, Davide; Cobianchi, Francesca; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2019)
The term SCIWORA (Spinal Cord Injury Without Radiographic Abnormality) indicates a clinically appreciable post-traumatic myelopathy in the absence of spinal column findings on radiographs and/or computed tomography (CT), but with pathologic findings at magnetic resonance imaging (MRI) in approximately two-thirds of cases. Affecting mainly children younger than 8 years, SCIWORA has been, however, also described in adult patients, but, due to the uncertainty of classification and frequent co-morbidity, the term “adult SCIWORA” has generated controversy, and some debate is still active. In this article, we report two different cases of adult SCIWORA involving cervical spinal cord, characterized by distinct and peculiar clinical features. A literature review and some clinical suggestions are also reported, mainly focused on the importance of a high level of suspicion in order to achieve a timely diagnosis and optimize the management and, consequently, the outcome of these trauma patients.